Penentuan penangkal radikal dan sun protection factor krim kombinasi ekstrak etanol kunyit dan temu putih - Pratiwi, Puspa Dwi; Yuliawati, Yuliawati; Sani K, Fathnur; Lestari, Uce (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Phytochemical studies about Curcuma genus such as Curcuma Longa and Curcuma zedoaria have shown the plants contains curcumin as the most isolated compound shown photoprotection agent and can be formulated as cream preparation. The concentration of Curcuma longa in cream preparation in this reseach was 0,5% and Curcuma zedoaria 0,5; 1; 1,5; 2; 2,5; and 3%. Cream preparations were physical evaluated of semi solid dosage form i.e pH organoleptic, spreadability, homogeneity, adhesion time and viscosity. The result was compared to SNI 16-4399-1996 (Indonesian Standard of UV protection preparation). All formulas were tested for radical scavenging activity using the DPPH method and SPF value determination. The results shown that formulas 3-6 met SNI requirements while formulas 1 and 2 did not met SNI from adhesion testing with results <1 second. Based on the antioxidant test results, it was found that formula 6 had the best antioxidant activity with lowest IC50 value of 126.69 ppm. It was linear as SPF value of formula 6 with 20.24 (ultra category). From this research, it was concluded that the greater of concentration of Curcuma zedoaria extract in cream preparation so free radical scavenger activity was better. Antioxidant activity is related to the SPF value of the preparation.